1997
DOI: 10.1111/j.1432-1033.1997.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of D‐Threonine Aldolase, A Pyridoxal‐5′‐Phosphate‐Dependentenzyme from Arthrobacter sp. DK‐38

Abstract: -EJB 97 0741/4 D-Threonine aldolase is an enzyme that catalyzes the cleavage of D-threonine into glycine and acetaldehyde. Its activity was found in several genera of bacteria such as Arthrobacter, Alcaligenes, Xanthomonus, and Pseudonzonas, but not in yeasts or fungi. The enzyme was purified to homogeneity from one strain, Arthrobacter sp. DK-38. The enzyme appeared to consist of a single polypeptide chain with an apparent molecular mass of 51 kDa. This enzyme, as we11 as L-threonine aldolase, requires pyrido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…The bound metal ions of the enzyme were subsequently analyzed with a mode ICPS-1000III sequential plasma spectrometer (Shimadzu, Kyoto, Japan); the enzyme so treated was determined to contain no detectable divalent cations, such as Mn 2ϩ , Mg 2ϩ , Co 2ϩ , Ni 2ϩ , Fe 2ϩ , and Ca 2ϩ , which were previously shown to be activators of the wild-type low specificity D-TA from Arthrobacter sp. strain DK-38 (16). Kinetic analysis further showed that the gel-filtrated enzyme had the same V max and K m values toward DLthreo-and DL-erythro-phenylserine as those of the metal-free ones treated with EDTA, supporting the finding that the purified enzyme contained no bound metal ions, at least no activating divalent cations.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…The bound metal ions of the enzyme were subsequently analyzed with a mode ICPS-1000III sequential plasma spectrometer (Shimadzu, Kyoto, Japan); the enzyme so treated was determined to contain no detectable divalent cations, such as Mn 2ϩ , Mg 2ϩ , Co 2ϩ , Ni 2ϩ , Fe 2ϩ , and Ca 2ϩ , which were previously shown to be activators of the wild-type low specificity D-TA from Arthrobacter sp. strain DK-38 (16). Kinetic analysis further showed that the gel-filtrated enzyme had the same V max and K m values toward DLthreo-and DL-erythro-phenylserine as those of the metal-free ones treated with EDTA, supporting the finding that the purified enzyme contained no bound metal ions, at least no activating divalent cations.…”
Section: Resultssupporting
confidence: 65%
“…strain DK-38 was used as the source of chromosomal DNA (16). E. coli XL1-Blue MRFЈ (recA1 thi endA1 supE44 gyrA46 relA1 hsdR17 lac/FЈ [proAB ϩ lacI q lacZ_M15::Tn10 Tet r ]) (Toyobo, Osaka, Japan) was used as a host for the gene cloning.…”
Section: Bacterial Strains Plasmids and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, D-type TA, acting on D-threonine and/or D-hydroxymethyltransferase, as a host, we occasionally observed allo-threonine, might include D-allo-TA, D-TA and low-specificthat E. coli GS245 could grow on the medium containing 1% ity D-TA, although low-specificity D-TA of Athrobacter sp. is glucose as the sole carbon source with a prolonged cultivation the only one identified (Kataoka et al, 1997b). All of the three time (Liu, J.-Q., Dairi, T., Itoh, N., Kataoka, M., Shimizu, S. L-type enzymes have been found to exist in nature.…”
mentioning
confidence: 99%